Genotyping and differential bacterial inhibition of Batrachochytrium dendrobatidis in threatened amphibians in Costa Rica - Abarca Alvarado, Juan Gabriel (2021)
Amphibians have declined around the world in recent years, in parallel with the emergence of an epidermal disease called chytridiomycosis, caused by the chytrid fungus Batrachochytrium dendrobatidis (Bd). This disease has been associated with mass mortality in amphibians worldwide, including in Costa Rica, and Bd is considered an important contributor to the disappearance of this group of vertebrates. While many species are susceptible to the disease, others show tolerance and manage to survive infection with the pathogen. We evaluated the pathogen Bd circulating in Costa Rica and the capacity of amphibian skin bacteria to inhibit the growth of the pathogen in vitro. We isolated and characterized – genetically and morphologically – several Bd isolates from areas with declining populations of amphibians. We determined that the circulating chytrid fungus in Costa Rica belongs to the virulent strain Bd-GPL- 2, which has been related to massive amphibian deaths worldwide; however, the isolates obtained showed genetic and morphological variation. Furthermore, we isolated epidermal bacteria from 12 amphibian species of surviving populations, some in danger of extinction, and evaluated their inhibitory activity against the collection of chytrid isolates. Through bioassays we confirmed the presence of chytrid-inhibitory bacterial genera in Costa Rican amphibians. However, we observed that the inhibition varied between different isolates of the same bacterial genus, and each bacterial isolation inhibited fungal isolation differently. In total, 14 bacterial isolates belonging to the genera Stenotrophomonas, Streptomyces, Enterobacter, Pseudomonas and Klebsiella showed inhibitory activity against all Bd isolates. Given the observed variation both in the pathogen and in the bacterial inhibition capacity, it is highly relevant to include local isolates and to consider the origin of the microorganisms when performing in vivo infection tests aimed at developing and implementing mitigation strategies for chytridiomycosis.